Нурмаханова А.С., Утешова С., Домакбаева А., Кенжебаева Ш.К., Атабаева С.Д., Асрандина С.Ш., Алыбаева Р.А. Тұзды жағдайлардың (NaCl) соя өсімдігінің (Glycine max) параметрлеріне және салыстырмалы су мөлшерімен жапырақтарының фотосинтез пигменттерінің мөлш: әл-Фараби атындағы Қазақ ұлттық университеті, Қазақстан, Алматы қ (Eurasian Journal of Ecology, 2018)
It was studied by NaCl in the content of in the leaves of soybean plants (Glycine max). The objects ofresearch were 3 varieties of soybean plants – Almaty, Vita and Lastochka. The plants were grown in thesoils with different concentration of NaCl – 0 (control), 0.01%, 0.1% for 14 days. Photosynthesis plays a key role in the process of growth and biomass accumulation. The length of the above-ground organsat a concentration of 0.1% NaCl in the Almaty variety decreased by 17%, in the Vita variety – by 19%,while in the Lastochka variety – by 28%. At a given concentration, the root length of varieties Lastochkaand Vita increased by 20% and 14%, respectively. With the action of 0.1% NaCl, the dry biomass of theaerial organs was reduced in all varieties. To a lesser extent, this indicator decreased in the Vita variety– by 17%, while in the other varieties Lastochka and Almaty – by 24%. At this concentration, the drymass of the roots only increased in the Vita variety by 32%, while in the other varieties it decreased. Inthe Lastochka variety, the dry mass of roots decreased by 9% , in Almaty variety – by 19%. The relativewater content (RWC) decreased in all varieties under the action of salinity. With the action of 0.1% NaClin Vita variety, this indicator decreased in the least degree – by 5%, in Almaty variety – by 8%, in Lastochka variety – by 15%. According to the results of research at concentration 0.1% NaCl, chlorophyllcontent was decrease in Vita and Almaty variety by 10% and 13%, respectively, and in Lastochka variety– by 14%. Content of chlorophyll b pigment content it was found to be 92% to control for Vita, 90%– for Lastochka and 89% – for Almaty variety. At 0.1% NaCl concentration, the concentration of carotenoids in Vita variety increased by 21%, while in Almaty and Lastochka varieties – by 16%. Thus, theamount of chlorophyll a and b has declined in the soybean varieties under salinity stress. It was shownthat the chlorophyll content in a resistant Vita variety has diminished to a minor degree in comparisonwith the other varieties.Key words: soybean, salinity, photosynthesis, chlorophyll, carotenoid, variety, resistance